PENDETEKSIAN TINGKAT KESEGARAN FILET IKAN NILA MENGGUNAKAN PENGUKURAN SIFAT BIOLISTRIK - Bambang Riyanto; Akhiruddin Maddu; Supriyanto . (Jurnal Pengolahan Hasil Perikanan Indonesia, 2012)
The development of modern rapid detection techniques of fish freshness requires a new perspective of the importance of physical chemical characteristics during deterioration process of quality fishery products. Positive correlation between the changes of fish body and the electrical properties is a basic information for support the development of the detection modern techniques of fish freshness. Studies of the electrical properties become more relevant along with the increasing demand of fish fast food consumption and fish product from freshwater aquaculture, which have been less done until now. The objective of this study was to detect freshness of tilapia fillets using bioelectrical properties. The result showed that level of freshness of tilapia fillet can be detected by using bioelectrical which has correlation with TVB, TPC and pH. The level of freshness of tilapia fillet during 16 hours observation showed that impedance tend to decrease with the range of 44.34-6.30 Ω, while dielectric constant and the electrical conductivity tend to increase with range of 178,208 to 2,812,764 and 0.065 to 0.487 S/m.Key words: bioelectrical, fish freshness, tilapia fillet, quality deterioration